Modern methodology with psychometric influence to improve the understanding the operative part of fractional numbers - Saucedo García, Myriam Liliana (2020)
The main objective of this article is to explain the positive influence of a new and innovative teaching methodology, applied to the mathematical operation of Rational Numbers (RN) of students; called Didactic Transposition (DT). The research was developed under the hypothetical-deductive design, whose sample was made up of a group of students from science majors at a private university. For this purpose, 2 measuring instruments were used, one the Check Sheet, and the other the Entry and Exit Knowledge Tests. It was concluded that the Didactic Transposition in question has a positive influence on the academic performance of students.